The Influence Of Reward And Punishment Systems On Teacher Work Motivation: A Study Of Senior And Vocational High Schools In Parung District, Bogor Regency - Irfan Rizka Akbar; Mitri Nelsi; Lily Setyawati Kristianti (Jurnal Ilmiah Multidisiplin, 2025)
This study explores the implementation of reward and punishment systems and their influence on teacher motivation in Senior and Vocational High Schools (SMA/SMK) in Parung District, Bogor Regency. Using a qualitative phenomenological approach, data were collected through in-depth interviews, observations, and documentation. The findings reveal that fair and transparent reward systems significantly enhance teacher motivation, while punishment, when applied objectively, supports discipline without reducing morale. However, inconsistencies, lack of flexibility, and limited transparency in implementation remain key challenges. SWOT and TOWS analyses further highlight strategic priorities, such as optimizing reward mechanisms, improving leadership communication, and minimizing non-pedagogical burdens. The study concludes that teacher motivation is shaped not only by institutional policies but also by leadership behavior, organizational culture, and contextual support. Strengthening these systems through adaptive and human-centered approaches is essential to foster sustainable performance and commitment among teachers. These insights offer valuable implications for school management and education policymakers in improving teaching quality.